Two Clinical Experiences with a New Sarcode: Potentised Mitral Valve in LM Potencies - Wadhwani, Gyandas G.; Kara, Shamini (Homœopathic Links, 2018)
Sarcodes are an important part of homeopathic materia medica, but their use is ambiguous. Mitral valve is yet another addition to the list but lacking in guidelines for therapeutic application based on homoeopathic drug proving data. Two clinical cases are outlined that empirically received potentised mitral valve in ascending LM potencies and experienced an improved quality of life that was corroborated with outcome in relation to impact of daily living (ORIDL). Potentised mitral valve may be a valuable addition to our materia medica after it has been proved according to homoeopathic guidelines.
Keywords: sarcode; homoeopathy; potentised mitral valve; LM potencies; outcome in relation to impact of daily living